2018
DOI: 10.1002/jcp.26389
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐182‐5p inhibited oxidative stress and apoptosis triggered by oxidized low‐density lipoprotein via targeting toll‐like receptor 4

Abstract: MicroRNAs (miRNAs) exhibit various roles in multiple biological processes and abnormal expression of miR-182-5p has been involved in many diseases. However, the role miR-182-5p in Atherosclerosis (AS) remains poorly understood. In our current investigation, an AS model was established by using oxidized low-density lipoprotein (ox-LDL) in RAW264.7 cells. miR-182-5p was markedly decreased in AS model dose-dependently and time-dependently. Additionally, CD36, oil-red staining levels, TC, and TG were inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…As we known, miRNAs regulate lives' activities by means of the protein indirect role and regulate target genes by binding to the 3'UTR of specific mRNAs and cause degradation or transcriptional inhibition of target genes [31][32][33][34][35][36]. Biological softwares were used to predict the possible target genes of miR-182-5p to investigate the mechanisms of these miRNAs in renal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we known, miRNAs regulate lives' activities by means of the protein indirect role and regulate target genes by binding to the 3'UTR of specific mRNAs and cause degradation or transcriptional inhibition of target genes [31][32][33][34][35][36]. Biological softwares were used to predict the possible target genes of miR-182-5p to investigate the mechanisms of these miRNAs in renal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-182-5p is up-regulated in Oral squamous cell carcinoma, breast cancer and hepatocellular carcinoma etc. [31][32][33][34][35][36]. However, the underlying mechanisms of miR-182-5p in the malignant behaviors of RCC are unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…And it has been demonstrated that miR‐182 participated in tumorigenesis and metastasis; it suppresses transcription of proinflammatory genes driven by TNF‐α (Miller et al, 2016; Wei, Lei, & Hu, 2015). In addition, it also negatively regulates immune responses in Atherosclerosis via targeting TLR4 and impacts the clonal expansion of activated helper T lymphocytes (Qin, Peng, Shi, & Ke, 2018; Stittrich et al, 2010). More important, miR‐182 may have an effect on immune response, cell proliferation, inflammation, and apoptosis‐related to the therapeutic effects of BM‐MSCs in ALI (Park, Jeong, Park, Yang, & Shin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that miR-182-5p contribute to anti-apoptotic and antioxidative processes. MiR-182-5p inhibited oxidative stress-induced apoptosis via targeting TLR4 [18].…”
Section: Discussionmentioning
confidence: 99%